Prawo międzynarodowe w Chinach w ujęciu historycznym (1000 p.n.e – 1912 n.e) - Muszyński, Mariusz (Kwartalnik Prawa Publicznego, 2015)
The main aim of the following article is to discuss two sets of rules. First, the rules in force in relations between the Chinese kingdoms at a time, when there was no uniform state of China, and cooperation existed at the local level, and second, standards used in contacts resulting from their unification or the conquest of the Chinese Empire until its fall. While the investigation of these issues does not cause particular difficulties, the problem is a still disputed scientific assessment of existing knowledge and its sources. There three reasons of that fact: first, especially in matters of distant time, knowledge comes in large part from myths and stories, which does not provide scientifically credible image; second, the international law in the modern sense is based on the rules of sovereignty and equality of bodies, whereas before the reunification of the Chinese state its external relations were of a different nature; third, when in China finally emerged relationships of sovereign nature in today‘s sense, they were unable to fix, because the Emperor Shi Huang-Ti has built China‘s unitary state of several sovereign countries, and in turn its external relations were based on the idea of Chinese universalism that had nothing in common with equality and sovereignty rules.